Developing Social Science Learning Videos in Elementary Schools During Covid-19 Pandemic - Yuanta, Friendha; Larasati, Diyas Age (Universitas Pahlawan Tuanku Tambusai, 2022)
Social Science is important subject in elementary school because many students are unable to comprehend the teacher's explanation. Developing valid and effective video learning media as learning resource for social studies learning in fifth graders of elementary school is needed, especially in online learning. This study used the ADDIE model, which has five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation (5) Evaluation. The subjects were 25 fifth graders in SDN Banyu Urip IX Surabaya. From validation results of media experts, material experts, and students' test results, video learning media is declared valid for social studies learning in the fifth grade. The result of the validation media were 91.45% for media experts, 92.34% from material experts, and 90, 50% for student tests. Then, the experts tested the effectiveness of using this video learning media. Test results show that students have achieved grades above the specified minimum achievement score with the average score of 90,75%. Thus, it can be concluded that video learning media is effective for learning.